Réponses

2013-08-06T21:59:15+02:00

                      (4x + 1) (2x − 5) + 3  =  (4x − 8)² − 8x(x − 9,875)

                  8x² − 20x + 2x − 5 + 3  =  16x² − 64x + 64 − (8x² − 79x)

                               8x² − 18x − 2  =  16x² − 64x + 64 − 8x² + 79x

                               8x² − 18x − 2  =  8x² + 15x + 64

     8x² − 8x² − 18x − 15x − 2 − 64  =  0

                                   −33x − 66  =  0

                                          −33x  =  66

                                                x  =  66/−33

                                                x  =  −2

 

 

           [Vérification :    [4(−2) + 1] [2(−2) − 5] + 3  =  (−8 + 1) (−4 − 5) + 3

                                                                         =  −7 × −9 + 3

                                                                         =  63 + 3

                                                                         =  66

 

                                  (4(−2) − 8)² − 8(−2)((−2) − 9,875)  =  (−8 − 8)² − (−16)(−11,875)

                                                                                    =  (−16)² − (16)(11,875)

                                                                                    =  256 − 190

                                                                                    =  66]